A Cross Sectional Study on the Cost Effectiveness of Antibiotics Used In Intensive Care Unit Patients Attending Tertiary Care Hospital - Rasheed, Razia Abdul; Devi P, Renuga; VijayalakshmiS, VijayalakshmiS; RajaTAR, RajaTAR; Senthil G, Senthil G; Kalaiselvi B, Kalaiselvi B; K M, Sudha; C.S, Brethis (Journal of Neonatal Surgery, 2025)
Background: In intensive care units (ICU), antibiotics are routinely prescribed to treat severe infections. cost-effectiveness analysis (CEA) is a technique used to assess the outcomes and costs of different strategies aimed at improving health, and has been utilized in various scientific disciplines. Aim And Objectives: To identify the most commonly prescribed antibiotics in ICU and To estimate the cost of antibiotics used in ICU patients. Materials And Methods: After IEC approval, This Cross sectional observational study was conducted in Medical Record Department of MAPIMS Hospital for 6 months. Sample size was found to be 385. The Indian Drug Review and the Current Index of Medical Specialties provide the brand cost of the medication Results: In this study, antibiotics were prescribed in 231 out of 312 case records accounting 74%. The cost per dose in ICU patients ranges from Rs 7.55 to Rs 800 (per dose). The most commonly prescribed injectable antibiotics were Ceftriaxonefollowed by Metronidazole, Piperacillin/Tazobactam, while, oral antibiotic was Tab. Doxycycline, Ciprofloxacin, Augmentin, Azithromycin, Taxim, ofloxacin and Linezolid Conclusion: The most cost-effective antibiotics were Tab. Doxycycline and Inj. Ceftriaxone.. To alleviate the financial burden on healthcare facilities, it is essential to conduct regular prescription audits and modify antibiotic policies.